The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00468-011-0643-x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genetic diversity of Erwinia amylovora: the causal agent of fire blight

Abstract: Erwinia amylovora is a polyphagous bacterium causing fire blight on apple, pear and over 130 other plant species belonging mainly to the Rosaceae family. Although E. amylovora is regarded as a very homogenous species, the particular strains can differ in pathogenic ability as far as their host range is concerned (e.g. those originating from Rubus or Maloidae plants) as well as by the extent of the disease they cause. It was found that strains originating from North America are generally more genetically hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 88 publications
0
18
0
Order By: Relevance
“…The typical symptom of the disease is necrosis of infected tissues with dissemination of the "scorched" phenotype from the infecting point, eventually involving the entire tree. [2] The production of exudates, called ooze, on infected fruits is another characteristic of the disease. Several factors help this pathogen to establish its pathogenicity.…”
mentioning
confidence: 99%
“…The typical symptom of the disease is necrosis of infected tissues with dissemination of the "scorched" phenotype from the infecting point, eventually involving the entire tree. [2] The production of exudates, called ooze, on infected fruits is another characteristic of the disease. Several factors help this pathogen to establish its pathogenicity.…”
mentioning
confidence: 99%
“…Unambiguous results from the ERIC-PCR complex fingerprinting of all tested virulent strains highlight the potential of the ERIC-PCR method as a fast and efficient tool to discriminate E. amylovora in routine diagnostics. Application of ERIC-PCR and other PCR fingerprinting methods for both diagnostic and epidemiological studies of E. amylovora and other species of Erwinia genus has already been reported (Puławska & Sobiczewski 2012).…”
Section: Discussionmentioning
confidence: 98%
“…The aim of our study was to analyse genetic and phenotypic features of several wild E. amylovora strains originating from different locations and time periods of the fire blight outbreaks in Hungary and Slovakia and compare them to the properties of E. amylovora strains from different localities (Zhao & Qi 2011;Puławska & Sobiczewski 2012). We decided to analyse the E. amylovora strains as potential carriers of antibiotic resistance given the long-standing history of antibiotic use in the control of fire blight outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…The plant pathogenic enterobacterium Erwinia amylovora is considered to be homogeneous in terms of phenotypic and genetic features (reviewed by Puławska and Sobiczewski 2012). recent comparative genomics studies confirmed that the chromosome of E. amylovora is highly conserved and has over 99 % amino acid identity among all strains tested (Mann et al 2013).…”
Section: Introductionmentioning
confidence: 95%